Application of rapid genotyping of Warfarin individualized pharmacogenetic variants in Warfarin therapy - Defa Huang; Fangfang Xie; Shengpeng Xiao; Minyang Cai; Die Hu; Baodian Ling; Fangsheng Wang; Xuan Lin; Fangli Song; Qi Wang; Tianyu Zhong (Scientific Reports)
Abstract Warfarin is the most widely used oral anticoagulant in clinical practice. The cytochrome P450 2C9 (CYP2C9), vitamin K epoxide reductase complex 1 (VKORC1), and cytochrome P450 4F2 (CYP4F2) genotypes are associated with warfarin dose requirements in China. Accurate genotyping is vital for obtaining reliable genotype-guided warfarin dosing information. The current method for individualized dosing gene polymorphism detection for warfarin has the disadvantages of being easily contaminated, time-consuming, expensive, and unsuitable for clinical use. Herein, we present a novel application, a multiplex fluorescent melting curve assay of whole-blood direct amplification of nested polymerase chain reaction (PCR), to genotyping single-nucleotide polymorphism (SNPs) rapidly that affect warfarin efficacy. This method requires only 1 µL of whole blood, no DNA extraction, takes less than 2 h, costs less than $1, and is able to accurately distinguish between different SNP sites. Polymorphic loci were detected in whole blood specimens of 181 clinical warfarin-administered patients through nested blood direct PCR fluorescence melting curve analysis and gene sequencing. The results of the nested blood direct PCR multiplex fluorescence melting curve technology were 100% consistent with those of sequencing—characterized by high accuracy and high specificity. The allele frequencies were 94.5% for A and 5.5% for C at CYP2C9*3 (rs1057910), 7.5% for G and 92.5% for A at VKORC1 (rs9923231), and 77.1% for G and 22.9% for A at CYP4F2*3 (rs2108622). For CYP2C9*2 (rs1799853), only allele C was detected, with a frequency of 100%. Warfarin doses were lower in the CYP2C9*1*1 genotype population than in the CYP2C9*1*3 population, lower in the VKORC1 (AA) population than in the VKORC1 (GG) population, and higher in individuals with the CYP4F2*3 mutation (GA/AA) compared with those with wild-type (GG). In summary, the detection and genotyping of four polymorphic SNP sites using a multiplex fluorescent melting curve assay of whole blood direct amplification through nested PCR is highly importance for guiding personalized warfarin anticoagulant therapy.